Analisa Getaran Mesin Milling Vertikal 1108 Terhadap Pengaruh Variasi Kedalaman Potong - Jupri Yanda Zaira; Agus Wijianto (Jurnal Elektro dan Mesin Terapan, 2020)
Rotating machines such as milling machines have spindle motor and feeding motor which can cause vibrations due to the rotation of the two motors. Apart from the vibrations of the two motors, the work piece eating process also greatly influences the level of vibration that occurs. In this research, milling machine number 1108 is used in the Caltex Riau Polytechnic Production Laboratory (PCR), and a face feeding process is used using three variations in cutting depth, namely 0.5 mm, 1 mm, and 1.5 mm, with each 15 data were taken in the time domain range of 4 seconds, besides the cutter used was a cutter end mill with a diameter of 30 mm. In knowing the level of vibration that occurs using vibration tester measuring instrument type VM-6370 which is owned by the PCR Production Machinery Laboratory. To test the vibrations generated, the position of the probe on the vibration tester is affixed to the workpiece when the feeding process occurs. Vibration results obtained in the form of displacement, velocity, and acceleration with three measurement directions, namely vertical, horizontal, and axial direction which are then analyzed so that the data obtained in the form of amplitude. From the research that has been done, it is obtained that the vibration results in the form of the largest amplitude in the axial direction with a cutting depth of 1.5 mm of feed is 0.164 mm.